BEYOND ANTIBIOTICS: NATURAL ALTERNATIVES IN THE FIGHT AGAINST BOVINE MASTITIS - Verly, Leonardo Bindelli; Rosa, Ana Carla Rangel; Gumiere, Tamiris da Silva; Andrade, João Victor; de Macêdo, Adriely Valerio; Perin, Isabelle Lucas Braga; Macedo, Maria Eduarda Dan; Marques, Cecília Fernandes Patta Muller; Costa, Gilvana de Oliveira; Caprini, Híllary Ozorio Gobeti; Santos, Mário Ferreira Conceição (Seven Editora, 2025)
Bovine mastitis is one of the main diseases that affect dairy farming, resulting in economic losses and impacts on animal health and milk quality. Conventional antibiotic treatment faces increasing challenges due to antimicrobial resistance, driving the search for natural and sustainable alternatives, such as the use of herbal medicines and essential oils from medicinal plants. Recent studies highlight the potential of several plant extracts with antimicrobial properties. Research has demonstrated the effectiveness of plants such as Psidium cattleianum, Tagetes minuta and Psidium guajava against Staphylococcus aureus and Corynebacterium bovis. Other studies have indicated that essential oils of species such as Origanum vulgare, Zataria multiflora and Thymus vulgaris are effective in controlling mastitis, reducing bacterial and somatic cell counts, in addition to improving the clinical conditions of the animals. Experiments carried out with animal models and dairy cows have shown promising results. Essential oils, applied intramammary or topically, have demonstrated antimicrobial, immunomodulatory and anti-inflammatory effects, without compromising milk quality or causing significant adverse effects. The use of natural alternatives, such as herbal medicines and essential oils, can reduce dependence on antibiotics, minimize risks of chemical residues in milk, and provide a more sustainable approach to mastitis management. The combination of these strategies with hygienic management practices and early diagnosis is essential for effective and integrated disease control, benefiting animal health and milk production.DOI: https://doi.org/10.56238/sevened2024.037-118